Pengaruh Pelatihan Dan Kompetensi Kerja Terhadap Kinerja Karyawan Pada PT Argenta Parakrama Artha Jakarta Pusat - Fadli, Roni; Seta, Anggada Bayu; Mulyani, Sri; Selviana, Nina (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the Effect of Training and Job Competence on Employee Performance at PT Argenta Parakrama Artha Central Jakarta. This type of research is quantitative with 78 employees. This study uses quantitative analysis methods. The sampling method is saturated by taking the entire amount filled in to be sampled. Data processing and analysis techniques use descriptive, data analysis instrument testing, classical assumption tests, correlation and determination tests, hypothesis tests. Job training and job competencies affect employee performance with the regression equation Y = 22.588, X1 = 0.182, X2 = 0.158. This is based on the correlation coefficient value of 0.964. Job Training affects Employee Performance based on the results of the hypothesis test, the t-count value> t-table (31.045> 1.992), the ρ value <Sig. 0.05 or (0.000 <0.05). Thus, H0 is rejected and H1 is accepted. Job Competence influences Employee Performance based on the results of the hypothesis test, the calculated t value > t table (2.129 > 1.992), the ρ value < Sig. 0.05 or (0.037 < 0.05). Thus, H0 is rejected and H1 is accepted. Job training and job competence influence employee performance Based on the results of the hypothesis test, the calculated F value > F table or (500.016 > 3.12) the ρ value < Sig. 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H3 is accepted. Keywords: Training, Work Competence, Employee Performance